Penguatan Strategi Penetapan Harga Berbasis Data Untuk Meningkatkan Daya Saing Usaha Kecil - Luthfi Ramadhan Putera; Nadia Kirana Cahyawati (Community : Jurnal Pengabdian Pada Masyarakat, 2026)
The digital economy requires small businesses to adopt more measurable pricing practices, yet many still rely on intuition, limiting margins and market adaptability. This community service program evaluates the effectiveness of data-based pricing mentoring in strengthening analytical capability and enhancing the internal competitiveness of small enterprises. A quantitative applied approach was implemented within a structured mentoring framework involving 20 small businesses that participated in training and recorded sales data for 14 days. Data were collected through observation, interviews, questionnaires, and transaction records, and analyzed using descriptive statistics and paired sample t-tests. The results show significant improvements in cost awareness, demand pattern analysis, and pricing decisions, with average margins increasing from 18.2% to 26.7%. Participants began adjusting prices more consistently based on data.  Margin growth and price stability are treated as proxies for internal competitiveness rather than for comprehensive market competitiveness. The program developed a simple, replicable mentoring model suitable for local economic empowerment initiatives.